(untitled) (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional De Tecnología, Ciencia Y Sociedad, 2019)
This paper presents the results of a study analyzing the perception of the students and their professor in a course on Technological Teaching and Research Resources involved in designing Service-Learning projects. The study took as its axis of inquiry a classroom group in which 61 first-year primary-school education degree students and their professor participated. The case study was used as the research methodology and document analysis, observation, ad hoc questionnaire and interviews as instruments for collecting information. The data collected enable us to confirm the effects produced on the organization of the teachinglearning process and on acquisition of functional learning. The findings show that Service-Learning is configured as a pertinent pedagogical methodology for favoring transfer of knowledge to real-life situations, getting students hooked on their learning process and developing digital, social and civic competence.